Galaxy: A platform for interactive large-scale genome analysis - Giardine, Belinda; Riemer, Cathy; Hardison, Ross C.; Burhans, Richard; Elnitski, Laura; Shah, Prachi; Zhang, Yi; Blankenberg, Daniel; Albert, Istvan; Taylor, James; Miller, Webb; Kent, W. James; et al. (Genome Research, 2005)
Accessing and analyzing the exponentially expanding genomic sequence and functional data pose a challenge for biomedical researchers. Here we describe an interactive system, Galaxy, that combines the power of existing genome annotation databases with a simple Web portal to enable users to search remote resources, combine data from independent queries, and visualize the results. The heart of Galaxy is a flexible history system that stores the queries from each user; performs operations such as intersections, unions, and subtractions; and links to other computational tools. Galaxy can be accessed at http://g2.bx.psu.edu.